Efficient Numerical Valuation of Continuous Installment Options (Advances in Applied Mathematics and Mechanics, 2018)
In this work we investigate the novel Kryzhnyi method for the numerical inverse Laplace transformation and apply it to the pricing problem of continuous installment options. We compare the results with the one obtained using other classical methods for the inverse Laplace transformation, like the Euler summation method or the Gaver-Stehfest method.